Effects of microbial organic fertilizer (MOF) application on cadmium uptake of rice in acidic paddy soil: Regulation of the iron oxides driven by the soil microorganisms. (15th August 2022) - Kong, Fanyi; Lu, Shenggao
Abstract: Rice often accumulates higher Cd from contaminated soils, thereby endangering human health. In this study, microbial organic fertilizer (MOF) was applied at the rate of 3, 4.5, and 7.5 t·MOF·ha −1, respectively, to passivate Cd in polluted soils. The goals of the field experiments were to understand how MOF reduces the uptake of Cd in rice by affecting the mobility and bioavailability of Cd in the rhizosphere soil. BCR sequential extraction analysis recorded that the addition of MOF decreased the content of available Cd and increased Cd residual fraction in soils. Compared with the control treatment, the application of 7.5 t·MOF·ha −1 significantly increased the yield of rice by 7.9% and decreased the Cd content in brown rice by 86.4%. The application of MOF strengthened the oxidation of iron by increasing the relative abundance of Fe-oxidizing bacteria (FeOB) Thiobacillus, and further increased the ratio of amorphous/dissociative iron oxides (Feo/Fed) and thickened the iron plaques on the root surface of rice. The spatial distribution of Cd and Fe on rice root indicated the key role of iron plaques in preventing Cd from entering rice. The structural equation model confirmed that MOF application regulated iron oxides by FeOB, dehydrogenase activity, and catalase activity, thereby reducing the Cd uptake of rice. Graphical abstract: Image 1 Highlights: Microbial organic fertilizer (MOF) increased the rice yield and reduced the Cd uptake of rice. MOF increased the abundance of iron-oxidizing bacteria and the activities of catalase and acid phosphatase. MOF thickened the iron plaque on surface of rice root to prevent Cd from entering rice. Application of more than 4.5 t ha −1 of MOF could ensure the safe rice production in lightly Cd-polluted soil.